Analysis of Irrigation Water Quality in Batang Lampasi - Yuni, Nola Rahma; Ekawaty, Reni (Sebatik, 2025)
Irrigation water quality plays a key role in determining soil conditions and crop productivity. This study assessed the irrigation water quality of the Batang Lampasi Irrigation Area by analyzing a composite sample and comparing the results with FAO quality standards. Laboratory analyses included physical parameters—electrical conductivity (EC), turbidity, temperature, and odor—and chemical parameters such as pH, salinity, total Fe, total Ca, total Mg, and Sodium Adsorption Ratio (SAR). The results indicated that all measured parameters, including EC (132 µS/cm), turbidity (6.78 FTU), pH (6.44), salinity (34.32 ppm), Fe (0.904 mg/L), Ca (1.891 mg/L), Mg (1.795 mg/L), and SAR (0.467 meq/L), fall within acceptable limits set by FAO. These findings confirm that Batang Lampasi irrigation water is suitable for agricultural applications and underline the need for consistent monitoring and the development of national irrigation water quality standards.